Microwave sintering of Zn-Nb doped barium hexaferrite synthesized via sol-gel method - Kanagesan, Samikannu; Hashim, Mansor; Jesurani, Sinnappan; Thirunavukarasu, Kalaivani; Ismail, Ismayadi (Scientific Research Publishing, 2014)
A series of polycrystalline M-type hexagonal ferrites with the formula BaFe12-2xZnx NbxO19 (x = 0.2, 0.4, 0.6, 0.8 mol%) have been synthesized by the sol-gel method. The composition and microstructure govern the magnetic properties of ferrites. The XRD analysis shows the formation of pure magneto plumbite phase without any other impurity phases. The Zn-Nb substitutions in barium hexaferrite have been confirmed through magnetic measurements. The results show that the magnetic properties are closely related to the distributions of Zn-Nb ions on the five crystallographic sites. The saturation magnetization and coercivity increase with increasing Zn-Nb concentration.